Sobre nó(s) : a precarização do trabalho na indústria têxtil sergipana - Araujo, Raab Lima Figueredo de (2020)
Justified by the need to adapt to the new times of financialization of the economy, we have witnessed, since the 1990s in Brazil, a “new” precariousness of work, which imposes itself as the center of the dynamics of flexible accumulation, aggravated by the historical heritage of a colonized country and, subsequently dependent. This “new” process, where old and new forms of work and employment coexist, as well as being combined and transformed, finds support in the neoliberal court policies introduced in the country in the 1990s and has its materialization revealed in the productive restructuring. In view of this, this work analyzes, within the framework of Brazilian particularities, how the precariousness of work manifests itself in the Sergipe textile industry from the 1990s onwards, considering a context characterized essentially by three different, but interdependent processes: productive restructuring, the globalization of capital and neoliberalism. For that, we used the dialectical method as Marx thought as an instrument for understanding our problems. The use of this scientific method was due to our quest to break away from the apparent and discover the relationships between the processes occurring in the constitutive totality of the precarious work process. Additionally, we trace a research path that includes both qualitative and quantitative research, with prevalence of the former. The methodological procedures used are: descriptive statistics, semi-structured interviews, literature review and fieldwork with systematic registration in a field notebook. We can conclude in this research that the precariousness of work is manifested today in the Sergipe textile industry, fundamentally, through the deepening of the intensification of work to inconceivable levels, but not only that, but also in the bad working conditions and in the growing process of alienation of the class -who-lives-from work.